Themenvorschläge für die zukünftige Sporck-Forschung - Kolda, Jindřich (Theatrum historiae, 2012)
The article summarises the crucial aspecys of the existing research concerning Franz Anton Sporck, an influential aristocrat of the Czech Baroque period, and presents several suggestions for further investigations in this field. It emphasises mainly the so far almost unknown history of the Sporck family and the most famous object of the Sporck family’s residence – Kuks.